Effect of Mare Nectaris on Feng-flavor Baijiu: an insight into the sensory evaluation and flavor analysis - Chen, Yuqi; Hu, Jinghui; Zhou, Feng; Meng, Xinli; Hu, Xuesong; Zhang, Jiaojiao; Han, Xinglin (Frontiers in Nutrition, 2025)
Feng-flavor Baijiu is a significant subtype of traditional Chinese baijiu that has considerable consumer popularity. This study examined how the quality of Feng-flavor Baijiu was affected by the various times that Mare Nectaris was used. The findings indicated that baijiu kept for a year in older Mare Nectaris (>10 years) was better than that in younger ones (< 5 years). Older Baijiu had richer honey, fruity, and Mare Nectaris-aromas, whereas fresh Baijiu had an astringent, lime flavor. Later in storage, old Mare Nectaris had a stronger effect on volatile taste constituents. OAVs >1 were present in 30 compounds in the old Mare Nectaris and 27 in the new ones. Propanal, lactic acid, acetaldehyde, and active amyl alcohol are linked to the “honey aroma.” This study may provide a theoretical basis for selecting suitable Mare Nectaris to enhance Feng-flavor Baijiu's flavor and sensory appeal.